Strategi Pembelajaran Adaptif untuk Statistik - Ro'fah Ro'fah; Andayani Andayani (PLD UIN Sunan Kalijaga, 2014)
This is a study which focuses on examining the problem in teaching-learning process of Statistic dealt by blind students at UIN Sunan Kalijaga in 2010. The investitigation is necessary as blind students should struggle to understand the subject. As matter of fact, Statistic is perceived as a problematic discipline in general, however, the situation worsen for blind students, was more problematic as it involves imagery thinking and visual perception such as graphics, symbols, images and on other side, needs a lot of practical exercises. This research utilizes qualitative method, through in-depth interview and Focus Group Discussion data collection. This involves 5 students and 2 lectures at UIN Sunan Kalijaga around the issues as follows: methods of teaching, class dynamic and evaluation. The problems and challenges dealt by students analyzed and thus recomendations are formulated in the end of study.